Superior Class Management during Covid-19 at MTs Islamiyah Barbaran Academic Year 2020/2021 - Candra Wijaya; Faisal Musa; Muhammad Arifin Ritonga; Munzir Munzir; Nurdin Nurdin (Budapest International Research and Critics University, 2021)
The Covid-19 pandemic has had a wide impact on various aspects of human life, especially education, so it needs to be reorganized or managed again, in accordance with the demands of implementing learning during Covid-19. The aim is that madrasahs still have an advantage over schools in general. MTs Islamiyah Barbaran is one of the madrasas in Mandailing Natal Regency which for approximately 8 years has implemented a superior class system learning pattern, to accommodate the demands or needs of smart or superior students. The ability of MTs Islamiyah Barbaran in managing superior classes so as to produce sufficient quality output or graduates makes this madrasah always in demand, and gets a good response from the community. In this regard, this study will examine the implementation of superior class management during covid-19 at MTs Islamiyah Barbaran, using a qualitative approach, the methods used in this study are the methods of interviewing, observation and documentation. The data analysis method uses qualitative descriptive analysis which consists of four stages, namely data collection, data reduction, data display and conclusion or verification. Withdrawing conclusions using the inductive method. The results of this study indicate that the principal of the madrasah has carried out superior class learning innovation management during the Covid-19 pandemic at Islamic Private MTs Barbaran TP. 2020/2021, namely by implementing several policies, such as online learning, flexibility of lesson hours, IT development, and maintaining daily protocols, by implementing management functions, namely planning, organizing, actuating, and controlling. In addition, committee empowerment is one of the main keys to the success of these MTs in managing superior classes.